Predictors of cancer risk in the long-term solid-organ transplant recipient. - Sherston, SN; Carroll, R; Harden, P; Wood, K (Lippincott Williams and Wilkins, 2014)
Malignancy is increasingly the leading cause of mortality in solid-organ recipients. Cancer incidence among the transplant population is overall threefold to fivefold higher than the general population with poorer outcomes for late-stage disease. Insights into the identification of patients at particular risk of developing a posttransplantation malignancy are imperative to ensure appropriate measures are instigated to reduce associated morbidity and mortality. This review focuses on potential clinical, immunologic, and genetic translational markers aimed at identifying long-term solid-organ transplant patients at high risk of developing cancer.